STUDI KASUS PENGARUH WAKTU DAN LAJU ALIR PADA PROSES REGENERASI MOLSIEVE MELALUI PEMANASAN PADA KILANG EKSTRAKSI NGL DI PT.PERTA-SAMTAN GAS - Haidi Tazaruddin; Fadarina HC; Abu Hasan (Politeknik Negeri Sriwijaya, 2022)
Molsieve adsorption plant which adsorp moisture content in feed gas until H2O below 0.1 ppmv at outlet vessel. After adsorption process, molsieve will saturated and need to regenerate for return molsieve capacity. Regeneration process are very important for adsorption capacity. Problem at extraction plant prabumulih is molsieve capacity will decrease after 3 month. Based of things that affect molsieve capacity, need to evaluate optimal regeneration as a maximum equipment limit. Meassurement parameter in this research is quantitiy of H2O not boiled or remain in molsieve, with heating time variable 3.5 hour , 4.0 hour, 4.5 hour, and 5.0 hour. Combined with flow rate variable 14.0 MMscfd, 14.5 MMscfd, 15.0 MMscfd, 15.5 MMscfd. Result in combination flow rate 15.5 MMscfd with heating time 5.0 hour have a mass H2O to boil up is 1.39387 ton and mass H2O remain in molsiev is 0.08019 ton. The writter found in flow rate 15.0 with heating time 5.0 hour is optimal combination based on equipment limitation. Writter suggest for replace equipment for raise up flow rate to maximal regeneration.